1. Read this: Calculus/Volume - Wikibooks, collection of open-content textbooks
2. Read this thread: http://www.mathhelpforum.com/math-he...functions.html
It's easy to find the volume of a cone, but how would you find the volume of a pyramid using integration? With height h and base length a. And if it's a SQUARE BASED pyramid.
Also...what's the antiderivative of (e^x)^2?
1. Read this: Calculus/Volume - Wikibooks, collection of open-content textbooks
2. Read this thread: http://www.mathhelpforum.com/math-he...functions.html
Here is one way.
We divide the pyramid into 4 congruent right triangular pyramids.
Meaning, cut the square-based pyramid along the two diagonals of the square base, vertically. (If you understand that, you're good ).
If the square base is by , then each diagonal is sqrt(2)* long.
Since the diagonals of a square are perpendicular and they bisect each other, then anyone of those 4 congruent right triangular pyramids has a base that is a right triangle whose hypotenuse is and whose legs are both sqrt(2) /2 = /sqrt(2) each.
We get the volume of one of these right triangular pyramids, multiply that by 4, and we get the volume of the right square-based pyramid.
In one of the right triangular pyramids:
Set the dV ---the element of the volume---anywhere from y=0 and y=h.
>>>dA = area of the dV
Say dV is a y below the apex, and the hypotenuse of the dA is x.
So, the area of the dA is (1/2)(x /srt(2))(x /sqrt(2)) = (x^2)/4
And the dV is [(x^2)/4]dy
-------------------------------------------------
We find the relationship of y and x.
In one vertical face of the right triangular pyramid, there are two right triangles;
Bigger right triangle has base = /sqrt(2), and height = h.
Smaller right triangle has base = x/sqrt(2), and height = y.
By proportion,
[ /sqrt(2)] /h = [x/sqrt(2) /y]
Cross multiply,
*y = h*x
So, x = ( /h)y
------------------
Hence, dV = [(x^2)/4]dy = (1/4)[ /h)^2 *y^2]dy
dV = (1/4)( ^2 /h^2)[y^2]dy
And so, for the whole right square-based pyramid,
V = 4{(1/4)( ^2 /h^2)INT(0 to h)[y^2]dy} ...going down is positive.
V = ( ^2 h^2)INT(0 to h)[y^2]dy
V = ( ^2 /h^2)[(y^3)/3](0 to h)
V = ( ^2 /h^2)[(h^3)/3 -0]
V = (1/3)( ^2)h
That is it.